A new species of Rain Frog from Namaqualand, South Africa (Anura: Brevicipitidae: Breviceps) - Channing, Alan (Zootaxa, 2012)
Breviceps branchi sp. nov. is described from coastal Namaqualand, South Africa. It is most similar to Breviceps namaquensis in colour pattern and overall form, from which it differs by hand and foot morphology and 16S rRNA sequence.